Metal-Free Synthesis of Dibenzoxazepinones via a One-Pot SNAr and Smiles Rearrangement Process: Orthogonality with Copper-Catalyzed Cyclizations - Hurst, Timothy E.; Kitching, Matthew O.; da Frota, Lívia C. R. M.; Guimarães, Keller G.; Dalziel, Michael E.; Snieckus, Victor (Synlett, 2015)
Reported is the transition-metal-free synthesis of substituted dibenzoxazepinones using a convergent domino SNAr–Smiles rearrangement–SNAr process. Substrate-scope investigations demonstrated the critical importance of ring electronic effects on the efficiency of the process. In addition, the orthogonality of this approach with transition-metal-catalyzed procedures was established.
Keywords: dibenzoxazepinones; domino reaction; Smiles rearrangement; nucleophilic aromatic substitution; heterocycles